3D simulation of single-event-transient effects in symmetrical dual-material double-gate MOSFETs. Issue 9 (August 2015) - Munteanu, D.; Autran, J.L.
Abstract: Dual-material double-gate (DMDG) structure is a promising structure for future ultra-scaled devices thanks to its capability to reduce short channel effects (SCEs) and hot-carrier induced effects (HCEs). This is due to a step in the surface-potential profile which screens the source side of the channel from drain-potential variations and reduces the drain electric field. In this work, we investigate the DMDG sensitivity to single-event transients. The impact of dual gate material workfunctions on the bipolar gain is particularly addressed. We show that DMDG is naturally less radiation immune than the usual single-material DG (SMDG) devices. Highlights: DMDG structure reduces SCEs and HCEs due to a step in the surface-potential profile. The DMDG behavior under irradiation has been compared with SMDG (single-gate material). DMDG has higher parasitic bipolar gain than SMDG. DMDG is naturally less radiation immune than the usual SMDG.